Comparison of 2D OPG image versus orthopantomogram from 3D CBCT from the forensic point of view - Eliasova, Hana; Dostalova, Tatjana; Prochazka, Ales; Sediva, Eliska; Horacek, Martin; Urbanova, Petra; Hlinakova, Petra (Legal medicine (Tokyo, Japan), 2021)
Forensic dental identification has employed traditionally 2D digital radiological imaging techniques. More recently, 3D cone beam computer tomography (CBCT) data, widely applied in clinical dentistry, have been gradually used. The purpose of this study was to compare the precision and quality of 2D digital orthopantomogram (OPG) and 2D OPG images generated from cone beam computed tomography (CBCT). The study sample consisted of 50 patients with archived conventional 2D OPG and 3D CBCT images. Patients signed an informed consent form to take part in our study. Measurements of the mandible, teeth and dental restorations were taken by two observers on calibrated 2D OPG and 3D CBCT-to-OPG images using measurement functionalities of DOPLHIN software. Acquired dimensions were compared side by side and images of fillings were superimposed. For better visual comparison and more efficient image registration, the methods of spline interpolation were used. The pairs of absolute measurements obtained from conventional OPG and CBCT-to-OPG-converted images were highly correlated (p < 0.05). However, larger, and horizontally measured distances were revealed to be more affected than shorter vertically taken measurements. In relative terms, CBCT-generated width/length indices of the canines and the first molars ranged from 84% to 99.8% of those acquired from traditional OPGs. In addition, corresponding points on the teeth and fillings were compared side by side and in superimposition. The average coincidence of images was 6.1%. The results revealed that for selected metric variables 2D OPGs and 3D CBCT-generated OPGs were complementary and could be used for forensic comparisons.
Keywords: Mandible; digitální zubní radiografie; Sensitivity and Specificity; senzitivita a specificita; Humans; Identification; trvalá zubní náhrada; Forensic Dentistry; Radiography, Panoramic; Dental Restoration, Permanent; Radiography, Dental, Digital; lidé; počítačová tomografie s kuželovým svazkem; Cone-Beam Computed Tomography; Cone beam computer tomography; rentgendiagnostika panoramatická; soudní stomatologie; Tooth; mandibula; Orthopantomogram; zuby; Dentistry